KELENTENG SIN TEK BIO, PASAR BARU, JAKARTA SEBAGAI LIVING MONUMENT DALAM KONSEP TIME & SPACE - Anderson S., Surya; Hadi, Rahadjeng Pulungsari (Multikultura, 2025)
Sin Tek Bio Temple is one of the ancient temples located in the Pasar Baru area, Central Jakarta. The various dynamics of time and space pose challenges for Sin Tek Bio Temple to continuously maintain its existence as a living monument in the Pasar Baru area. The conditions of time and space influence the worship symbols, labels, and public perspectives regarding Sin Tek Bio Temple. The research method used in this study is a qualitative-descriptive method combined with field studies. The researcher conducted the study through several stages, namely literature review, field observation, and interviews with experts. The findings of this research present a detailed explanation of the time and space dynamics that affect the symbols and labels associated with Sin Tek Bio Temple, as well as an in-depth account of how the temple manages to endure the various challenges it has faced and will continue to face.